Pre-Ozonation-Coagulant Interactions in Direct Filtration - (:unkn) unknown (IWA PUBLISHING, 2010)
Pre-ozonation-coagulant interactions effects in relation to the coagulant type and dosage in direct filtration of surface waters were investigated. The performance of the process was evaluated by monitoring the effluent quality and head loss development through the filter bed. Two identical pilot scale filter columns filtering the same raw water were operated in parallel. The raw water was brought from Omerli Reservoir in Istanbul. Before filtering, the raw water flow was split into two equal flows. One of the streams was pre-ozonated and the other was aerated using contact chambers with equal volumes equipped with same number and type of diffusers. In coagulation experiments, one of the filters was operated using aluminum sulfate as a coagulant while the other one was run with ferric chloride. For similar filter run times, the effluent quality was always better with pre-ozonation compared to aeration. It was also observed that, aluminum sulfate application gave more favorable results for both particle and turbidity removal compared to ferric chloride. Ives' filterability index which incorporates the important filtration design parameters such as: effluent quality, the head loss and the velocity of filtration into a dimensionless number was used for the comparison of the experimental results.
Keywords: direct filtration; ozonation; aluminum sulfate; ferric chloride; head loss; particle count; turbidity